2019
DOI: 10.1109/access.2019.2936664
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Requirement Change Management Challenges Between in-House and Global Software Development: Findings of Literature and Industry Survey

Abstract: Requirement changes are inevitable, and Requirement Change Management (RCM) is a complex process in software development. In-house software development and Global Software Development (GSD) are two widely used development approaches and there is a need to explore the RCM commonalities and differences in the two development approaches. The primary objective of this study is to identify the challenges that influence RCM in both approaches. First, we have implemented Systematic Literature Review (SLR) and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…As stated by Portillo-Rodriguez [4] and Anwer [12] there is a need for tools that support software engineering processes in the context of DSD and more specially requirements management. Most of the existing tools considers issue tracker as the main feature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by Portillo-Rodriguez [4] and Anwer [12] there is a need for tools that support software engineering processes in the context of DSD and more specially requirements management. Most of the existing tools considers issue tracker as the main feature.…”
Section: Discussionmentioning
confidence: 99%
“…to minimize problems such as: geographic dispersion, control and coordination breakdown, communication, team engagement and sociocultural differences. Moreover, It is important to propose and analyze tools in real scenarios [4] [12]. We describe some existing requirements management tools in the following paragraphs.…”
Section: Related Workmentioning
confidence: 99%
“…Anwer et al [43] identified the in-house development and offshore development challenges during RCM. They further differentiated the challenges based on their impact on the project development and categorized them using T-test, Chi-square test, and regression analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Lai and Ali, 17 Ramzan and Ikram, 52 Akbar et al, 53 Kamal et al, 54 and Shafiq et al 1 underlined that less effort had been directed towards developing the RCM tools and techniques in the GSD context. Anwer et al 55 mentioned that eight out of 10 software firms working in GSD faced RCM problems owing to poor planning and ineffective RCM standards and tools. The RCM process faced additional challenges that do not exist in the collocated development environment (e.g., language, cultural, and time zone differences) 56,57 …”
Section: Literature Review and Motivationmentioning
confidence: 99%